Nurses' perception of the multidisciplinary team approach of care for adolescent mothers and their children in Ugu, KwaZulu-Natal - Desiree Govender; Saloshni Naidoo; Myra Taylor (AOSIS, 2019)
Background: Adolescent childbearing has numerous consequences on maternal health, child health and the well-being of society. Because of the high-risk nature of adolescent pregnancy, a multidisciplinary team (MDT) approach is recommended to achieve satisfactory pregnancy outcomes. Aim: The aim of this study was to explore nurses' perceptions of the MDT approach in the continuum of care for adolescent mothers and their children. Setting: The study was conducted in a local district hospital in Ugu, KwaZulu-Natal. Methods: An explorative and descriptive qualitative study design was used. The first author and hospital staff (clinical midwives and the clinical manager of obstetrics and gynaecology) collaborated on the development of the focus group discussion (FGD) guide to explore nurses' perception of the MDT approach of care for adolescent mothers and their children. A total of three FGDs were conducted. Data were analysed using thematic analysis. Results: Six overarching themes emerged from the data analysis which included professional benefits of adopting the MDT approach of care for adolescent mothers and their children, barriers to the multidisciplinary collaboration, clinical benefits of adopting the MDT approach of care for parenting adolescent mothers, problems and needs of adolescent mothers, and nurses' reasons regarding their willingness to participate in a multidisciplinary collaboration in the care of parenting adolescent mothers. Conclusion: In the opinion of nurses, the MDT approach of care for adolescent mothers and their children is an important strategy to improve maternal and child health outcomes. This study has important implications for the design of an intervention.